Immune-related ureteritis and cystitis induced by immune checkpoint inhibitors: Case report and literature review - Li, Jun; Yu, Ya-Fen; Qi, Xiao-Wei; Du, Yuan; Li, Chun-Qing (Frontiers in Immunology, 2023)
Immune checkpoint inhibitors (ICIs), including anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA4) and anti-programmed death cell protein 1 (anti-PD1), are increasingly prescribed in metastatic carcinoma therapy. Immune checkpoint inhibitors-related kidney injury is gradually recognized by clinicians. However, immune-related ureteritis and cystitis go undiagnosed easily. We report three cases of PD-1 monoclonal antibody (PD-1mAb)-related ureteritis and cystitis. We further carried out a review of the literatures about ICIs-related ureteritis and cystitis. The cases in our reports manifest urinary irritation, sterile pyuria, gross hematuria, hydronephrosis, dilation of ureters, and acute kidney injury. Urinary irritation improved effectively, urinalysis and renal function returned to normal after glucocorticoid therapy. During ICIs therapy, urinalysis, renal function and urinary imaging examination are recommended monitored regularly. It contributes to identify immune-related ureteritis /cystitis earlier to alleviate urinary symptoms and immunologic urinary tract injury through glucocorticoid therapy efficiently, meanwhile avoid the abuse of antibiotics.